2021
DOI: 10.1002/cld.1137
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus in India: Challenges and Successes

Abstract: The past decade has seen a paradigm shift in the management of hepatitis C virus (HCV) infection with the development of direct-acting antiviral (DAA) drugs. In 2016, the World Health Organization laid out the Global Health Sector Strategy on viral hepatitis, which endorsed the elimination of viral hepatitis by 2030. In a country like India with a large population and diverse socioeconomic status and cultural practices, the path to HCV elimination has indeed thrown up both challenges and success stories. CHall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…Whilst there is no HCV national registry in India and thus epidemiology is scarce, HCV seroprevalence has been reported to range between 0.09%-5.2% across various Indian states. 32 , 33 , 34 The most prominent HCV genotype was genotype 2 which contrasts with findings from a previous epidemiological analysis of HCV which showed that genotype 3 was the most prevalent in India. 35 One possible biological explanation for the concurrent identification of HCV and SARS-CoV-2 is suggested by emerging evidence which shows that HCV increases the expression of the SARS-CoV-2 entry receptor ACE2 in hepatocytes, leading to enhanced entry of both HCV and SARS-CoV-2 into hepatocytes.…”
Section: Discussioncontrasting
confidence: 87%
“…Whilst there is no HCV national registry in India and thus epidemiology is scarce, HCV seroprevalence has been reported to range between 0.09%-5.2% across various Indian states. 32 , 33 , 34 The most prominent HCV genotype was genotype 2 which contrasts with findings from a previous epidemiological analysis of HCV which showed that genotype 3 was the most prevalent in India. 35 One possible biological explanation for the concurrent identification of HCV and SARS-CoV-2 is suggested by emerging evidence which shows that HCV increases the expression of the SARS-CoV-2 entry receptor ACE2 in hepatocytes, leading to enhanced entry of both HCV and SARS-CoV-2 into hepatocytes.…”
Section: Discussioncontrasting
confidence: 87%
“…Although India has a high burden of HCV, screening tests are not used that widely even among the high-risk populations. This can be exemplified by the fact that only nearly 2% of the Indian blood banks could perform the screening test, nucleic acid amplification test for HCV [12] . When it comes to treatment, only 4 direct-acting antivirals are available in India, namely, ledipasvir, sofosbuvir, velpatasvir, and daclatasvir, limiting treatment for patients with prior treatment failure, and those with genotype 3 and cirrhosis.…”
Section: Challenges and Implicationsmentioning
confidence: 99%
“…The extremely high costs also prohibit treatment in many cases. Even if treatment is provided for free, about 15% of the patients do not adhere to the plan [12] . That is why hepatitis C has a high case rate in India.…”
Section: Challenges and Implicationsmentioning
confidence: 99%
“…5 The disease affected nearly 4.7 to 10.9million population as per 2015 global estimates. 6 Furthermore, the mortality rates continue to remain high and are estimated to be as high as 96,000 every year. 5 The major challenge in HCV treatment is the prevalence of various HCV genotypes and subtypes and the varying effectiveness of each direct-acting antiviral drug (DAA) against each genotype.…”
Section: Introductionmentioning
confidence: 99%